In-Situ Analysis of the in-Plane Current Distributions in an Electrolyte-Supported Planar Solid Oxide Fuel Cell by Segmented Electrodes. (10th January 2017) - Ochiai, Tatsuhiro; Nakajima, Hironori; Karimata, Takahiro; Kitahara, Tatsumi; Ito, Kohei; Ogura, Yusuke; Shimano, Jun
Abstract : In the planar solid oxide fuel cell (SOFC), the fuel/oxidant distributions cause current and temperature distributions over the electrodes under the separator ribs and flow channels. Optimized designs of the separator to improve the output power and chemical/thermo-mechanical durabilities of practical stacks require numerical models validated by insitu current distributions measured. We have therefore addressed in-situ measurements of inplane spatial current variations of an electrolyte-supported planar SOFC by segmented cathodes opposing the anode rib and flow channels. We focus on the effect of the rib width on the spatial current distribution. We model the current and hydrogen partial pressure distributions by finite element modeling so that the model agrees with the insitu measurements by the segmented cathodes with determining the exchange current densities, electrode porosities, electrolyte ion conductivities, and electrode ion/electron conductivities.